Prototyping of Regenerative Braking System Based on Hybrid Energy Storage System in Electric Vehicle Prototype E-Trail Bangkits - Romadhon HS, Maulana Ray; Sudarmanta, Bambang (JMES The International Journal of Mechanical Engineering and Sciences, 2024)
The use of a Hybrid Electrical Energy Storage System (HESS) using a battery and supercapacitor in regenerative braking system on BANGKITS E-Trail prototype has the potential to offer greater power density and cycle life. The aim of the study was to maximize the recovery of energy during braking using the system, while improving the performance of E-Trail BANGKITS. The proposed regenerative braking system based on HESS was designed and fabricated while considering energy recovery capacity, and maximum electsamarical load. After fabrication, the system was tested for its efficiency, in energy recovery and to drive the vehicle using recovered energy. The tests were conducted in two steps, which are stationary, and dynamic tests, using a variation of motor and vehicle speed. The results of the tests showed in regenerative mode, system can recover up to 4410 J of energy with 41% efficiency with ascending trend as motor speed increases, while in drive mode, system can successfully drive the vehicle at 1430W power draw, and 14.8s of discharge time. In vehicle performance test, system was capable of generating braking force of 427.92N at 36% braking contribution. System can also extend the driving range of the vehicle by 2.4% of test route distance.